The Persian Whitman : Beyond a Literary Reception - Fomeshi, Behnam M. (Iranian studies series (Leiden, Netherlands), 2019)
Walt Whitman, a world-renowned poet and the father of American free verse, is read by diverse audiences around the world. Literary and cultural scholars have studied Whitman's interaction with and influence in social, political, and literary movements of different countries. Despite his work's continuing presence in Iran, Whitman's reception in this country has remained unexplored, and, particularly due to contemporary political circumstances, Iranian reception of Western literature is a field still under-researched. The Persian Whitman examines Whitman's reception in Iran and explores a new phenomenon born in dialogue between the Persian culture and the American poet.